Đặc tính điện hóa của điện cực Ti/RuO2 chế tạo từ dạng sol-gel muối ruteni - Kết, Nguyễn Duy; Phượng, Phạm Thị; Hùng, Nguyễn Đức (Vietnam Journal of Chemistry, 2014)
Ti/RuO2 electrode formed by solgel of rutheniumsalt and thermal decomposition techniques on titanium was studied by using cyclic voltammetry and galvanodynamic polarisation in solution: H2SO4 0.5 M and NaCl 3%. The electrocatalytic activity of Ti/RuO2 electrode for the oxygen and chlorine evolution reaction depends on the propeties of titanium surface, the temperature of heating treatment and the number of cyclic voltammetry. With the RuO2 coated on the anodized titanium surface the electrocatalytic activity for oxygen and chlorine reaction is 5 time higher by 400oC. But the ratio of iCl2/iO2 is on the non anodized titanium surface in NaCl 3% is higher.